The Limitations of Notary Legal Liability in Indonesia towards Disputed Authentic Deeds - Santa Indah Theresia Pardosi (Nurani Hukum, 2022)
This study aims to determine the legal liability of a notary as a general official for doing authentic deeds when disputed in a court by the parties. The research type is normative juridical by using a law approach and a conceptual approach. The data collection technique is by studying literature in the form of primary legal materials and secondary legal materials. The data analysis technique uses a qualitative descriptive method. The result of the study shows that the notary who commits acts against the law can be sued by the parties for criminal, civil, or administrative liability.Â  Meanwhile, the notary cannot be blamed for the disputes that arise later between the parties if the notary has acted according to the procedure. It is because the notary has only liability for the formal truth, namely in recording what was conveyed by the parties as stated in the authentic deed. A notarial deed that is not appropriate or defective will lose its authenticity, so it is only considered valid as a private deed.